Impact of Temperature Inversion on the Distribution Shifts of Turkish Red Pine (Pinus brutia Ten.) and Black Pine (Pinus nigra Arnold.) in the Karıncalı Region, Bursa – Orhaneli - Mustafa Yilmaz; Salih Parlak; Kamil Erken; Mehmet Kalkan (South-East European Forestry)
Topographic diversity leads to climate and vegetation differences over short distances. A significant example of these differences is temperature inversion, where cold air accumulates in hollows and concave areas, resulting in lower temperatures in lower zones and affecting the distribution limits of plant species. In this study conducted in the Karıncalı region of Orhaneli, Bursa, the effect of temperature inversion on the natural distribution of Turkish red pine (Pinus brutia Ten.) and black pine (Pinus nigra Arnold.) stands was investigated. Measurements made with temperature sensors placed between 500-600 m altitude for two years showed that although black pine is generally distributed at higher altitudes, it is located below the red pine zones due to temperature inversion. Especially in the lower zones, recorded low temperatures have revealed the cold adaptation advantage of black pine. Temperature inversion affects the distribution limits of plant species, reshaping ecosystem structure and interspecies competition. This highlights the necessity of considering temperature inversion areas in forestry activities. In reforestation projects to be carried out in areas where inversion conditions are effective, the selection of cold-resistant species is of vital importance for the success of the applications.